US Policies In Asia-Pacific Between 2008-2018: From G2 To New Containment - Rodríguez-Rincón, Sthefany (2020)
The aim of this paper is to analyze the policies of the United States towards the Asia-Pacific region, between 2008 and 2018, mainly the US containment strategy against China. After the victory of Barack Obama as president of the United States, the United States policy towards this region experienced several changes. The former cooperation project named G2 was replaced by a geostrategic proposal called “Pivot”. This proposal changed, both the United States politics and economics in this region by being involved in initiatives as the TPP and military alliances as the Quadrilateral Security Dialogue. China interprets this proposal as a containment strategy due to United States alliances with other countries in the region and the constant intervention of this country in the territorial disputes in the South China Sea.